PEMANFAATAN EKSTRAK KAYU MERBAU UNTUK PEREKAT PRODUK LAMINASI BAMBU - Adi Santoso; Ignasia Maria Sulastiningsih; Gustan Pari; Jasni Jasni (Jurnal Penelitian Hasil Hutan, 2016)
The report describes the use of adhesive made from merbau wood extract (Intsia Spp.) which is allowed to copolymerize with resorcinol, formaldehyde under alkaline conditions, and tapioca as an extender. The adhesive was used to manufacture three-ply composite board consisting of a back and core layers made from sengon (Falcataria mollucana),  and jabon (Anthocephalus chinensis), while the face layer was made either one of  three bamboo  species, namely, andong (Gigantochloa pseudoarundinacea), mayan (Gigantochloa robusta Kurz.), and bitung (Dendrocalamus asper Schult. F.). Result shows that physical-mechanical properties of  the composite board with using adhesive by formula (% of weight ratio) Merbau extract : Resorcinol 50% : Formaldehyde 37% : Extender = 100 : 10 : 10 : 5) were similar with to those of products made of  synthetic phenolic adhesive and classified as an exterior quality type with E0 or F**** types of low formaldehyde emission.